Analysis of the Influence of Corporate Social Responsibility (CSR), Profitability, and Good Corporate Governance (GCG) on Stock Prices in Property and Real Estate Companies Listed on the Indonesia Stock Exchange (IDX) and the Malaysia Stock Exchange for 2013-2021 - Kristin Monica Br Sembiring; Narumondang Bulan; Erwin Abu Bakar (PT FORMOSA CENDEKIA GLOBAL, 2023)
The study aims to investigate and analyze how Corporate Social Responsibility (CSR), Profitability—which includes Return on Asset (ROA), Return on Equity (ROE), Net Profit Margin (NPM), and Good Corporate Governance (GCG), which includes Managerial Ownership, Institutional Ownership, Board of Directors, and Audit Committee—affect stock prices in real estate and property in Indonesia and Malaysia. 21 firms were utilized as examples out of the 178 that was listed on the Indonesia Stock Exchange and Malaysia Stock Exchange between 2013 and 2021. Panel Data Regression was used to examine the data. The study's findings suggested that institutional ownership and return on equity both had a small but substantial impact on stock prices in Indonesian and Malaysian property and real estate businesses. Contrarily, the variables Managerial Ownership, Board of Directors, Return on Asset, Net Profit Margin, and Audit Committee had no impact on the stock price.